The effect of training methods and hand–eye coordination on students' forehand shot accuracy - Oka Rahma Warzuqni; Roma Irawan; Masrun Masrun; Kamal Firdaus (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examined the effects of training methods and hand–eye coordination on forehand drive accuracy among members of the Table Tennis Activity Unit at Padang State University. A quasi-experimental 2 × 2 factorial design was applied to 20 players selected through purposive sampling. Participants were trained using multiball or combination training methods and categorized based on high or low hand–eye coordination. Data were analyzed using two-way ANOVA. The results showed that the multiball training method significantly improved forehand drive accuracy and that a significant interaction existed between training method and hand–eye coordination. Multiball training was more effective for players with high coordination, while no significant difference was found for those with low coordination.